From memories to philosophy: on the 100th anniversary of E. V. Il’enkov - Lobastov, Gennady V. (Journal of the Belarusian State University. Sociology, 2024)
The events around the name of the world-class philosopher Eval’d Vasil’evich Il’enkov are briefly reproduced. The central problems of his scientific work are described. The importance of the scientist’s theses on the subject of philosophy is noted. The dynamics of E. V. Il’enkov’s creative thought is traced, in particular, the gradual transition from the study of the subject of philosophy to the study of personality as a central figure of historical development in the context of the teachings of K. Marx.
Keywords: E. V. Il’enkov; philosophy; thinking; being; consciousness; philosophy in society; the social meaning of philosophy; truth; misconception; education; personality